The "Bringing into Cultivation" Phase of the Plant Domestication Process and Its Contributions to In Situ Conservation of Genetic Resources in Benin. (22nd May 2012) - Vodouhè, R.; Dansi, A.
Abstract : All over the world, plant domestication is continually being carried out by local communities to support their needs for food, fibre, medicine, building materials, etc. Using participatory rapid appraisal approach, 150 households were surveyed in 5 villages selected in five ethnic groups of Benin, to investigate the local communities' motivations for plant domestication and the contributions of this process to in situ conservation of genetic resources. The results indicated differences in plant domestication between agroecological zones and among ethnic groups. People in the humid zones give priority to herbs mainly for their leaves while those in dry area prefer trees mostly for their fruits. Local communities were motivated to undertake plant domestication for foods (80% of respondents), medicinal use (40% of respondents), income generation (20% of respondents) and cultural reasons (5% of respondents). 45% of the species recorded are still at early stage in domestication and only 2% are fully domesticated. Eleven factors related to the households surveyed and to the head of the household interviewed affect farmers' decision making in domesticating plant species. There is gender influence on the domestication: Women are keen in domesticating herbs while men give priority to trees.